Single‐Layered and Single‐Crystalline Graphene Quantum Dots from 2D Polycyclic Compounds. (1st September 2016) - Yuan, Biao; Xie, Zheng; Sun, Xingming; Yan, Jun; Chen, Ping; Zhou, Shuyun
Abstract : Single‐layered and single‐crystalline graphene quantum dots (GQDs) are exfoliated from 2D conjugated polycycle compounds. The fluorescence properties of the GQDs are determined by the size of the precursors and are responsive to the pH of the GQDs solution. The synthesis method is novel and simple, and can be a general route to exfoliate 2D polycyclic compounds, including macrocyclic compounds, fused ring compounds, heterocyclic compounds and block molecules of 2D planar nanomaterials and polymers into single‐layered or single‐crystalline GQDs.